Wireless power supply for rotating piezoelectric actuators in high performance aeronautic drilling systems. Issue 4 (2nd October 2017) - Goenaga, E.; Ferrieux, J.-P.; Frey, D.; Roudet, J.
Abstract: In this paper, a contactless power transfer system is presented. It is designed to supply piezoelectric actuators with a low frequency signal and a DC offset. A power electronic structure based on a full bridge PWM inverter, a resonant capacitor, an inductive rotating transformer which works at low frequencies and the piezoelectric actuator is presented and modeled. The behavior of the system is analyzed regarding the variation of the transformer's coupling coefficient and the resonant capacitor value. Then, an optimization tool is presented where magnetic and power properties of the system are optimized in terms of electrical performances and volume. An embedded passive electronic system, that creates the mandatory DC offset for the actuator, is shown. Experimental results obtained with the prototype are exposed and compared to the simulations. Based on these results, a new version with a secondary quasi-resonant topology has been studied allowing both to reduce the size of the transformer and the global efficiency.